2023
DOI: 10.1111/jan.15649
|View full text |Cite
|
Sign up to set email alerts
|

Converting qualitative data into quantitative values using a matched mixed‐methods design: A new methodological approach

Abstract: BackgroundQuantifying qualitative data as part of mixed‐methods research (MMR) can add to the study results' analysis. Comparable results may reinforce the conclusions, while differences hold an opportunity for an in‐depth discussion. To date, there is little guidance for researchers seeking to quantify their qualitative data.ObjectivesDescribing conversion of qualitative data to quantitative values, comparison with matched questionnaire results, discussing the benefits of this process and the matched MMR desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Codes were then interpreted quantitatively by cross tabulating against the demographic variables, to see if this could enhance the presentation of the results or identify and confirm any patterns (Halevi Hochwald et al, 2023). However, no significant relationships were identified, and as such, it was decided not to include quantitative data for the themes generated, which can often cause a loss of meaning due to an arbitrary assignment of values or losing important relationships and patterns through reducing data to a single dimension (Halevi Hochwald et al, 2023;Hanbury et al, 2011;Miles & Huberman, 1994).…”
Section: Methods For Data Analysismentioning
confidence: 99%
“…Codes were then interpreted quantitatively by cross tabulating against the demographic variables, to see if this could enhance the presentation of the results or identify and confirm any patterns (Halevi Hochwald et al, 2023). However, no significant relationships were identified, and as such, it was decided not to include quantitative data for the themes generated, which can often cause a loss of meaning due to an arbitrary assignment of values or losing important relationships and patterns through reducing data to a single dimension (Halevi Hochwald et al, 2023;Hanbury et al, 2011;Miles & Huberman, 1994).…”
Section: Methods For Data Analysismentioning
confidence: 99%
“…An additional limitation is the study’s reliance on self-reported questionnaires to evaluate perceptions of learning quality, for the possibility of response bias and subjectivity. Future research could incorporate objective measures or observational methods to complement self-reported data, or use a complex mixed-method design [ 40 ] providing a more holistic understanding of clinical learning quality.…”
Section: Limitations and Recommendations For Future Researchmentioning
confidence: 99%
“…Additionally, this special issue highlights unique ways of studying well-established phenomena, including methodologies borrowed and adapted from other disciplines, as well as new methodologies withnursingastheontologicalbase.Asnursingresearchadvances, emerging methodologies are playing a pivotal role in reshaping the future of healthcare. The adoption of clique percolation (Lee et al, 2023) and netnography methods (Smith et al, 2023) Furthermore, novel methods to convert qualitative data into quantitative values (Halevi Hochwald et al, 2023) or reduce retraumatization of researchers and nurses taking part in important longitudinal studies (Conolly et al, 2023) hold great promise for the nursing profession. Halevi Hochwald et al ( 2023) described the benefits and methods of translating qualitative data to quantitative values using a matched mixed method research design.…”
Section: Under S Tudied Nur S Ing Phenomenamentioning
confidence: 99%
“…Halevi Hochwald et al ( 2023) described the benefits and methods of translating qualitative data to quantitative values using a matched mixed method research design. They suggested that this methodology allows for further valuable discussion within research papers and allows better integration and easier presentation of results (Halevi Hochwald et al, 2023). Conolly et al (2023) critically evaluated the concepts of harm and retraumatization in the research process and explored the ethical consequences of carrying out research in relation to distressing topics.…”
Section: Under S Tudied Nur S Ing Phenomenamentioning
confidence: 99%